The innate immune axis drives aortic dissection pathogenesis through inflammation and presents novel therapeutic targets - Xu, Can; Chen, Wenping; Nie, Xinyu; Xu, Rui; Feng, Xingyue; Chen, Zhifen; Wang, Dongjin (Frontiers in Immunology, 2025)
Acute aortic dissection (AAD) is a life-threatening cardiovascular emergency characterized by aortic layer separation and false lumen formation, with high mortality rates. Emerging evidence highlights the critical role of innate immunity in AD pathogenesis. Innate immune activation drives AAD progression through multiple mechanisms, including macrophage polarization (M1/M2 imbalance), neutrophil extracellular trap (NET) formation, and inflammasome activation. These processes amplify vascular inflammation via cytokine storms (IL-1β, IL-6, TNF-α) and oxidative stress, further promoting matrix metalloproteinase activation and smooth muscle cell phenotypic switching. The cGAS-STING pathway, triggered by mitochondrial DNA release, and TLR signaling act as central hubs connecting vascular injury to innate immune responses. This review synthesizes recent advances in the molecular mechanisms of AAD, focusing on aortic wall structural alterations, dysregulated signaling pathway, including TGF-β, Ang II, STING, and TLR cascades, and immune-inflammatory responses mediated by innate immune components. A deeper understanding of these innate immune components may lead to improved diagnostic biomarkers and targeted therapies for AAD management.